2014
DOI: 10.5194/hess-18-2033-2014
|View full text |Cite
|
Sign up to set email alerts
|

Climate change impacts on the hydrologic regime of a Canadian river: comparing uncertainties arising from climate natural variability and lumped hydrological model structures

Abstract: Abstract. Diagnosing the impacts of climate change on water resources is a difficult task pertaining to the uncertainties arising from the different modelling steps. Lumped hydrological model structures contribute to this uncertainty as well as the natural climate variability, illustrated by several members from the same Global Circulation Model. In this paper, the hydroclimatic modelling chain consists of twenty-four potential evapotranspiration formulations, twenty lumped conceptual hydrological models, and … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
26
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(27 citation statements)
references
References 55 publications
1
26
0
Order By: Relevance
“…Ficklin et al (2014) indicate that uncertainty in snowmelt model parameters can lead to statistically significant differences in hydrological climate change projections. However, Seiller and Anctil (2014) show that, for a catchment in Canada, the snow module is a much smaller source of uncertainty than hydrological model structure, PE formulation and natural variability. Studies looking at PE estimation using climate model data have shown that it can be an important source of uncertainty ) but accounting for the influence of higher carbon dioxide concentrations on plant stomata, as here, can reduce the future PE increases that may otherwise be expected (Bell et al 2011;Rudd and Kay 2016).…”
Section: Discussionmentioning
confidence: 95%
“…Ficklin et al (2014) indicate that uncertainty in snowmelt model parameters can lead to statistically significant differences in hydrological climate change projections. However, Seiller and Anctil (2014) show that, for a catchment in Canada, the snow module is a much smaller source of uncertainty than hydrological model structure, PE formulation and natural variability. Studies looking at PE estimation using climate model data have shown that it can be an important source of uncertainty ) but accounting for the influence of higher carbon dioxide concentrations on plant stomata, as here, can reduce the future PE increases that may otherwise be expected (Bell et al 2011;Rudd and Kay 2016).…”
Section: Discussionmentioning
confidence: 95%
“…It has shown good results in Canada [47][48], especially, it has produced relatively good flow and water temperature simulations for the Fourchue River [40], which is the study area. The CEQUEAU model is a semi-distributed hydrologic model which takes into account the hydro-physiographic characteristics of the basin [49].…”
Section: Water Temperature Model: Cequeau Modelmentioning
confidence: 99%
“…Many formulae exist for estimating PE, ranging from the physically-based Penman-Monteith formula (Monteith 1965) to much simpler empirical formulae like that of Oudin et al (2005), and the choice can affect the results of subsequent hydrological modelling (e.g. Seiller andAnctil 2014, Kay andDavies 2008). There is much disagreement on the best approach when deriving PE from climate model data for future periods, with concerns about empirical formulae not explicitly including changes in all the influencing variables, but also concerns about data quality when using more complex formulae (see discussion of Kay et al 2013).…”
Section: Introductionmentioning
confidence: 99%